Employment and mental health of youth in Egypt: Does job security matter? - Maye Ehab (Elsevier, 2023)
Youth in Egypt face compounded difficulties from the widespread use of fixed-term and informal employment. However, the relationships between these jobs and mental health remain to be evaluated among employed youth. This paper investigates the effect of transitioning from non-employment into employment on the mental health of youth younger than 30 years old. I differentiate jobs based on security and formality, focusing on the variation between permanent, temporary, casual/seasonal, and informal employment. Using nationally-representative panel data, I estimate the impact of various employment transitions on mental health outcomes by applying a matched difference-in-differences design. Transitioning to temporary, seasonal, and casual jobs has no significant effect on mental health compared to staying in non-employment. The psychological benefits are gendered. The gain for women is on the prevalence of mental illness, while men see an improvement in the depth of mental illness. For women, transitioning to a formal job provides the highest mental health rewards, while for men, a transition to a permanent job yields the highest mental health rewards. More consideration for the various types of employment and mental illness is required when studying non-standard employment.